Improving the affinity of tomato grafted on Solanum torvum using an intermediate rootstock - Miguel, A.; Marsal, J. I.; Goto, Rumy [UNESP]; Bautista, A. San; López-Galarza, S.; Pascual, B.; Maroto, J. V. (My University, 2011)
Most of the interspecific rootstocks (Lycopersicum esculentum × L. hirsutum) used in grafted Spanish tomato crops are resistant to Meloidogyne nematodes, but the 'Mi' resistance gene does not work well at high soil temperatures. Ralstonia solanacearum is a bacterial disease usual in tropical areas, but recently identified with low incidence in several European countries. This disease could be controlled by grafting tomato on Solanum torvum, which is also resistant to Meloidogyne. However, S. torvum and tomato have low grafting affinity, which could be improved using an intermediate rootstock. Some cultivars of eggplant have a relatively good affinity with tomato and complete affinity with S. torvum. In this study we compared two tomato cultivars (one resistant to Verticillium dalihae, Fusarium oxysporum v. lycopersici race 2 and Meloidogyne spp., and one non-resistant) grafted onto 'Beaufort' (Lycopersicum esculentum × L. hirsutum), 'Torvum Vigor' (Solanum torvum) and also with an intermediate grafting of eggplant ('Cristal') between tomato and S. torvum, with nongrafted plants as controls. This arrangement was carried out in two cropping cycles (winter-spring and summer-autumn). In both cycles, plants grafted onto S. torvum, both single or double grafted, yielded less than those grafted onto 'Beaufort' or nongrafted plants. In the spring cycle, no differences were found between single and double-grafted plants using S. torvum rootstocks, but in the autumn cycle double grafted plants had higher yields than the single grafted plants. The severity of nematode infections, in terms of reducing yields, and/or hypothetical infections of Ralstonia, will determine the utility of this technique in tomato production.
Keywords: Grafting; Incompatibility; Lycopersicum esculentum; Nematodes; Soil diseases; Bacteria (microorganisms); Fusarium oxysporum; Lycopersicon esculentum; Meloidogyne; Nematoda; Ralstonia; Ralstonia solanacearum; Solanum; Solanum melongena; Solanum torvum